2019
DOI: 10.14202/vetworld.2019.418-423
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant enterobacteria colonize commercial day-old broiler chicks in Nigeria

Abstract: Aim: This study was conducted to isolate generic enterobacteria from day-old broiler chicks in Nigeria, determine the antibacterial resistance profile, and assess multidrug resistance. Materials and Methods: The birds were sourced from five purposively-selected hatcheries (identified as A, B, C, D and E) in Southwest Nigeria. Non-duplicate cloacal swabs were collected from a total of 75 (15 birds per hatchery) randomly selected apparently healthy birds. Sampling was done in three batches of five chicks per ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
(73 reference statements)
0
16
1
Order By: Relevance
“…It is important to highlight the high AMR obtained to CIP, NAL, AMP, SXT, AZM, and TMP in this study ( Koga et al., 2015 , Hussain et al., 2017 , Ayandiran et al., 2018 , EFSA and ECDC (European Food Safety Authority and European Centre for Disease Control), 2018 ). Slight variations in AMR rates among isolates in these studies could be because of the different analysis methods employed, the different management systems set up, level of AMR in hatcheries, and use of antibiotics in the study areas ( Okorafor et al., 2019 ). Specifically for AMP, TMP, and SXT, one hypothesis that could explain the results obtained in this study is that these antibiotics are permitted in Spain as therapeutic agents for bacterial infections, and as reported above for CST, they have been used as a growth promoter in animal production systems for several years ( PRAN, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to highlight the high AMR obtained to CIP, NAL, AMP, SXT, AZM, and TMP in this study ( Koga et al., 2015 , Hussain et al., 2017 , Ayandiran et al., 2018 , EFSA and ECDC (European Food Safety Authority and European Centre for Disease Control), 2018 ). Slight variations in AMR rates among isolates in these studies could be because of the different analysis methods employed, the different management systems set up, level of AMR in hatcheries, and use of antibiotics in the study areas ( Okorafor et al., 2019 ). Specifically for AMP, TMP, and SXT, one hypothesis that could explain the results obtained in this study is that these antibiotics are permitted in Spain as therapeutic agents for bacterial infections, and as reported above for CST, they have been used as a growth promoter in animal production systems for several years ( PRAN, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in this study demonstrated the importance of AMR shedding from breeders to 1-day-old chicks. Several authors have shown that 1-day-old chicks are potential reservoirs of multiresistant enterobacteria obtained vertically from breeders ( Jiménez-Belenguer et al., 2016 , Projahn et al., 2017a , Projahn et al., 2017b , Okorafor et al., 2019 ). MDR bacteria could be transmitted through contaminated eggshells and/or from parent stock to hatchery ( Projahn et al., 2017a , Daehre et al., 2017 , Osman et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated a relationship between AMR genes in breeders and those present in their progeny. Several studies have investigated the role of vertical transmission in resistant genes spreading ( Projahn et al., 2017a , 2017b ; Okorafor et al., 2019 ). Authors have studied how MDR bacteria and resistance genes in poultry could be transferred ( Borjesson et al., 2016 ; Daehre et al., 2017 ; Osman et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Poultry sell in wet markets usually come from intensive operations with a wide AMU. As a result, cases of 1-day old chickens harboring multidrug-resistant bacteria have been reported in LMICs [ 76 , 138 , 139 , 140 , 141 ].…”
Section: Potential Risk Of Antimicrobial Resistance Human Exposurementioning
confidence: 99%